Efficacy of high-dose methylprednisolone as a first-line therapy in adult patients with idiopathic thrombocytopenic purpura - (:unkn) unknown (WILEY, 1998)
Fifty-seven adult patients with idiopathic thrombocytopenic purpura (ITP) were treated with either conventional-dose prednisolone (CDP) (1 mg/kg/d, 36 patients) or high-dose methylprednisolone (HDP) (30 mg/ kg/d, 21 patients), as first-line treatment. Patients in the HDP arm responded more rapidly (4.7 v 8.4 d), with a higher response rate (80% v 52.7%), and without severe side-effects. One quarter of the patients (3/12) who were nonresponsive to CDP achieved complete remission when they were treated with HDP. The findings suggest that HDP may be a more effective first-line treatment than CDP for adult ITP, and it may also be preferred for life-threatening cases of ITP. However, these results must be confirmed by a randomized study prior to any change in the current practice of employing CDP as first-line treatment for adult ITP.
Keywords: idiopathic thrombocytopenic purpura; high-dose methylprednisolone; PULSE THERAPY; INTRAVENOUS METHYLPREDNISOLONE; MEGADOSE METHYLPREDNISOLONE; IMMUNOGLOBULIN